Biological, Psychological, and Sociocultural Factors Contributing to the Drive for Muscularity in Weight-Training Men - Schneider, Catharina; Rollitz, Laura; Voracek, Martin; Hennig-Fast, Kristina (Frontiers in Psychology, 2016)
The drive for muscularity and associated behaviors (e.g., exercising and dieting) are of growing importance for men in Western societies. In its extreme form, it can lead to body image concerns and harmful behaviors like over-exercising and the misuse of performance-enhancing substances. Therefore, investigating factors associated with the drive for muscularity, especially in vulnerable populations like bodybuilders and weight trainers can help identify potential risk and protective factors for body image problems. Using a biopsychosocial framework, the aim of the current study was to explore different factors associated with drive for muscularity in weight-training men. To this purpose, German-speaking male weight trainers (N = 248) completed an online survey to determine the extent to which biological, psychological, and sociocultural factors contribute to drive for muscularity and its related attitudes and behaviors. Using multiple regression models, findings showed that media ideal body internalization was the strongest positive predictor for drive for muscularity, while age (M = 25.9, SD = 7.4) held the strongest negative association with drive for muscularity. Dissatisfaction with muscularity, but not with body fat, was related to drive for muscularity. The fat-free mass index, a quantification of the actual degree of muscularity of a person, significantly predicted drive for muscularity-related behavior but not attitudes. Body-related aspects of self-esteem, but not global self-esteem, were significant negative predictors of drive for muscularity. Since internalization of media body ideals presented the highest predictive value for drive for muscularity, these findings suggest that media body ideal internalizations may be a risk factor for body image concerns in men, leading, in its most extreme form to disordered eating or muscle dysmorphia. Future research should investigate the relations between drive for muscularity, age, body composition, internalization, dissatisfaction with muscularity and body-related self-esteem using longitudinal study designs. Limitations concern the cross-sectional design of the study, self-reported body composition measures and the homogeneity of the sample.